The Effects Of Accelerated Weathering On The Tensile Properties Of Kenaf Reinforced Biocomposites. (April 2019) - Abdullah, A. H.; Bakar, A. A.; Ismail, H.; Kahar, A. W. M.; Debnath, S.
Abstract: HDPE/soy powder/kenaf biocomposites with and without compatibilizer were prepared by the incorporation of kenaf core filler at different loadings into HDPE/soy powder biocomposites with an internal mixer. The prepared specimens were exposed to ultraviolet light in a weathering chamber for 500, 1000, and 2000 hours with scheduled water sprays to simulate the rain condition. The effects of accelerated weathering on the composite samples were investigated by tensile test, colour change analysis, and field emission scanning electron microscopy. The analysis conducted on the samples showed reductions in the tensile strength and considerable change in colour with the increasing accelerated weathering time.